Metal and metalloids concentration in Galapagos fish liver and gonad tissues. (December 2021) - Franco-Fuentes, Eduardo; Moity, Nicolas; Ramírez-González, Jorge; Andrade-Vera, Solange; González-Weller, Dailos; Hardisson, Arturo; Paz, Soraya; Rubio, Carmen; Gutiérrez, Ángel J.
Abstract: The Galapagos Islands are one of the best-preserved archipelagos in the world. We sampled individuals of six demersal and three pelagic species. The metal concentration of liver and gonad tissues were analyzed by Inductively Coupled Plasma Optical Spectrometry. Findings suggest none of the pelagic species showed metallic concentrations that could pose a risk to their health or reproductive capacity. S. violacea and P. clemensi Zn levels were higher in liver than in gonads, indicating that these species could be in their reproduction period. Zn risk toxicity for the study species is negligible. High concentrations of Cd were found in the liver of C. princeps, C. affinis and P. albomaculatus which could cause morphological and physiological alterations. We hypothesize that the high metal concentrations found in the demersal species could come from the volcanism of the islands, since no major sources of anthropogenic metal contamination can be found in the archipelago. Highlights: Thunnus albacares showed a wide range of metal concentrations. Our data shows pelagic species had low metal concentration Gonad metal content suggest Seriolella violacea and Pontinus clemensi could be in their reproduction period. Caulolatilus princeps and Caulolatilus affinis showed the highest metallic concentrations. Metal concentrations in Hyporthodus mystacinus do not agree with the bioaccumulation process.